Analysis of the Impact of Illegal Gold Mining (PETI) Using Suction Dredges ("Dompeng") on Water Pollution in Tanah Sepenggal Lintas District, Bungo Regency - Dinda Azizul Fairah; Sonia Yulia Friska; Eni Martiza; Tantri Eka Purwaningsih; Anastasya Yolanda (The Future of Education Journal, 2026)
This study aims to analyze the impact of illegal gold mining (Penambangan Emas Tanpa Izin [PETI]) using suction dredges (dompeng) on water pollution in Tanah Sepenggal Lintas District, Bungo Regency. The study employed a qualitative approach, with data collected through field observations, interviews, and documentation conducted in July 2025. The findings reveal that PETI activities have caused significant deterioration in river water quality, as indicated by increased turbidity, brownish discoloration, and unpleasant odors. In addition, mining activities have resulted in river sedimentation, degradation of riparian vegetation, and a decline in aquatic biodiversity. Mercury contamination was also detected at concentrations exceeding the established environmental quality standards, rendering the river water unsuitable for daily domestic use. These environmental impacts have adversely affected the health and socioeconomic conditions of local communities. Although various initiatives have been undertaken by the government, local communities, and relevant stakeholders to curb illegal mining activities, their implementation continues to face challenges, particularly in monitoring and law enforcement. This study concludes that illegal gold mining using dompeng has severe consequences for aquatic ecosystems and requires more comprehensive and sustainable management strategies.